Ethics in Empirical Research - Theoretical Considerations Regarding Education and Communication - Andronic, Ana Maria Teodora (Acta Universitatis Danubius. Communicatio, 2022)
Ethical standards are, in theory, as important, or even more relevant than the actual research itself. But the journey that led educators, academics, researchers and other specialists to arrive at modern research ethical standards was a long, disputed and unethical voyage. Ethical research is based on principles such as social value, informed consent, fair subject selection, a favorable risk-benefit ratio, scientific validity, respect and many others. Ethics takes into consideration a constellation of factors, which will be discussed and detailed in this article. The analysis compares the perspectives of micro and macro-ethics, and of research ethics in various domains of activity, such as psychology, education and linguistics.